New perspectives on climate, Earth surface processes and thermal hydrological conditions in high latitude systems - Aalto, Juha (Helsingin yliopisto, 2014)
Climate, Earth surface processes and soil thermal hydrological conditions drive landscape development, ecosystem functioning and human activities in high latitude regions. These systems are at the focal point of concurrent global change studies as the ongoing shifts in climate regimes has already changed the dynamics of fragile and highly specialized environments across pan Arctic. This thesis aimed to 1) analyze and model extreme air temperatures, soil thermal and hydrological conditions, and the main Earth surface processes (ESP) (cryoturbation, solifluction, nivation and palsa mires) controlling the functioning of high latitude systems in current and future climate conditions; 2) identify the key environmental factors driving the spatial variation of the studied phenomena; and 3) develop methodology for producing novel high quality datasets. To accomplish these objectives, spatial analyses were conducted throughout geographical scales by utilizing multiple statistical modelling approaches, such as regression, machine learning techniques and ensemble forecasting. This thesis was based on unique datasets from the northern Fennoscandia; climate station records from Finland, Sweden and Norway, state of the art climate model simulations, fine scale field measurements collected in arctic alpine tundra and remotely sensed geospatial data. In paper I, accurate extreme air temperature maps were produced, which were notably improved after incorporating the influence of local factors such as topography and water bodies into the spatial models. In paper II, the results showed extreme variation in soil temperature and moisture over very short distances, while revealing the factors controlling the heterogeneity of ground thermal and hydrological conditions. Finally, the modelling outputs in papers III and IV provided new insights into the determination of geomorphic activity patterns across arctic alpine landscapes, while stressing the need for accurate climate data for predictive geomorphological distribution mapping. ...